Effects of sintering parameters and Nd doping on the microwave dielectric properties of Y2O3 ceramics. Issue 7 (15th May 2016) - Zhang, Xiaorong; Fan, Guifen; Wang, Xiaohong; Lei, Wen; Fei, Liang; Lu, Wenzhong
Abstract: Y2 O3 ceramics with good dielectric properties were prepared via co-precipitation reaction and subsequent sintering in a muffle furnace. The effects of Nd doping and sintering temperature on microwave dielectric properties were studied. With the increase in sintering temperature, the density, quality factor ( Q × f ), and dielectric constant ( ε r ) values of pure Y2 O3 ceramics increased to the maximum and then gradually decreased. The Y2 O3 ceramics sintered at 1500 °C for 4 h showed optimal dielectric properties: ε r =10.76, Q × f =82, 188 GHz, and τ f =−54.4 ppm/°C. With the addition of Nd dopant, the Q × f values, ε r, and τ f of the Nd: Y2 O3 ceramics apparently increased, but excessive amount degraded the quality factor. The Y2 O3 ceramics with 2 at% Nd2 O3 sintered at 1460 °C displayed good microwave dielectric properties: ε r =10.4, Q × f =94, 149 GHz and τ f =−46.2 ppm/°C.